DOTting the path to doom: how acceleration of histone methylation leads to leukemia - Bach, Christian; Slany, Robert (Cancer Cell, 2014)
Epigenetic control mechanisms are central to normal and malignant hematopoiesis. In this issue of Cancer Cell, Deshpande and colleagues demonstrate that AF10, an interaction partner of the histone methyltransferase DOT1L, is essential for efficient H3K79 methylation, thus regulating HOX-gene transcription and transformation in myeloid leukemia.
EVALuna2:25714